Against Narration Sickness in Higher Education: Implications of Paulo Freire’s Banking Concept of Education on Achievement of University Education Objectives in Kenya in the light of the U Universities Act 2012 - Amukowa, Wycliffe (My University, 2013)
This paper discusses how a pedagogy void of narration sickness would be conducive for the achievement of objectives of education. According to Paulo Freire (2005), a careful analysis of the teacher-student relationship at any level, inside or outside the school, reveals its fundamentally narrative character. This relationship involves a narrating Subject (the teacher) and patient, listening objects (the students). The contents, whether values or empirical dimensions of reality, tend in the process of being narrated to become lifeless and petrified. Education is suffering from narration sickness. This paper endeavours a finding of lessons from Paulo Freire’s observation that could make solid contributions towards attaining the objectives of university education in Kenya as outlined in the Universities Act 2012.
Keywords: Education; Objectives; Reforms; Pedagogy; University